Language Style Used by The Main Character In Hala: A Sociolinguistic Study - Salsabila, Jovanka; lestari, kurnia; Vionitaretami, Canna Vionitaretami (Institut Agama Islam Negeri Palopo, 2023)
Everyone has their own unique way of communicating through language. This language style is used depends on the circumstances of a conversation, for example by the context and conversation participants. Language style is a sociolinguistic study that examines how people communicate with others who speak in a range of styles. The object of this research is the Hala movie, a movie that tells about a Muslim teenager who lives in America and has to face between two cultures. This study focuses on the analysis of language style used by the main character in the Hala movie and also several factors that influence the main character to speak in a different language style. This movie is analyzed with language style theory of Martin Joos, the five clock theory which is frozen style, formal style, consultative style, casual style, and intimate style, also the Janet Holmes’s theory of social factors why people speak with different language style. This research use qualitative descriptive method where the data are collected from the movie. The results of this research indicate that the main character used different language style and some factors influenced her to speak with different language style. There are 49 data found of language style used by the main character, consultative style with 7 data, casual style with 18 data, intimate style with 11 data, formal style with 13 data, and 0 data for frozen style. However, there are 62 of social factors that influenced Hala to speak with different language style, participants with 28 data, settings with 7 data, and contexts with 27 data.